The S&P 500 Index and the “Super 6” Technology Stocks in the Pandemic Crisis - Nenkov, Dimiter (Research Papers, 2021)
The subject of this research is the performance of the US stock market in the conditions of the current Covid-19 pandemic. The interest to this issue is provoked by the quite illogical record-high levels of US stock-market indices, while the economy is seriously injured by the pandemic. The broad S&P 500 index is analyzed in this case, as representative for the whole US economy. Historical performance of the index is reviewed, using its key financial indicators, such as EPS, EPS growth, as well as PE and PBV market ratios. The purpose is to check whether recent growth of stock prices is supported or not by these key indicators.After a significant, but brief collapse in March 2020, caused by the pandemic, the stock market began to pursue new price records in the months that followed. In the process of the study, it becomes evident that a very important factor for the continued increase of the S&P 500 levels during the period April-August are the so called “Super 6” technology stocks, included in the index. This is the reason why special attention is paid to some important performance indicators of these 6 companies. The elaborate comparative analysis of the above set of indicators does not support the high growth of stock prices in recent years and within 2020. It does not provide sound arguments in favor of the high current level of the S&P 500 as a whole, nor does it for the prices of the “Super 6” technology stocks.